2006
DOI: 10.1161/01.res.0000215343.89308.93
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelial Nitric Oxide Synthase in the Regulation of SREBP Activation by Oxidized Phospholipids

Abstract: Abstract-Oxidized-1-palmitoyl-2-arachidonyl-sn-glycero-3-phosphorylcholine (Ox-PAPC), found in atherosclerotic lesions and other sites of chronic inflammation, activates endothelial cells (EC) to synthesize chemotactic factors, such as interleukin (IL)-8. Previously, we demonstrated that the sustained induction of IL-8 transcription by Ox-PAPC was mediated through the activation of sterol regulatory element-binding protein (SREBP). We now present evidence for the role of endothelial nitric oxide synthase (eNOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 44 publications
3
69
0
Order By: Relevance
“…This pathway directly regulates IL-8 transcription through binding to a novel gamma-interferon activation sequence (GAS) element in the IL-8 promoter. The sustained regulation of IL-8 transcription was found to be mediated by cholesterol depletion and the activation of the uncoupled eNOS/SREBP pathway 28,29 , which is sustained for up to 16 hours after Ox-PAPC treatment in HAEC. Increased binding of SREBP to an SRE element in the IL-8 promoter was also demonstrated.…”
Section: Chemokine Expressionmentioning
confidence: 95%
See 2 more Smart Citations
“…This pathway directly regulates IL-8 transcription through binding to a novel gamma-interferon activation sequence (GAS) element in the IL-8 promoter. The sustained regulation of IL-8 transcription was found to be mediated by cholesterol depletion and the activation of the uncoupled eNOS/SREBP pathway 28,29 , which is sustained for up to 16 hours after Ox-PAPC treatment in HAEC. Increased binding of SREBP to an SRE element in the IL-8 promoter was also demonstrated.…”
Section: Chemokine Expressionmentioning
confidence: 95%
“…46 Gharavi et al demonstrated that superoxide produced by uncoupled e-NOS also is a source of ROS. 28 Increased mitochondrial metabolism may also play a role as has been seen for fatty acid oxidation products 47 . Whatever the source of ROS, Ox-PAPC clearly induces transcription of anti-oxidant enzymes including HO-1, glutathione synthase, thioredoxin reductase and glutathione reductase.…”
Section: Regulation Of Oxidative Stressmentioning
confidence: 98%
See 1 more Smart Citation
“…Again, in human aortic ECs, VEGF receptor 2 is reported to regulate ERK1/2-mediated activation of the transcription factor sterol regulatory element-binding protein 1 (SREBP-1), and the subsequent transcription of tissue factor, LDL receptor, and IL-8 [197]. Endothelial NOS has been reported to play a role in the activation of SREBP by oxPAPC [198].…”
Section: Up-regulation Of Chemokines Inflammatory Cytokines and Growmentioning
confidence: 99%
“…The expression of COX-2 appears to be modulated by oxPLs, in a cAMP-response-element-binding-protein-dependent and PPAR -dependent manner [207]. OxPLs may also increase NO production, with possible anti-inflammatory effects, including down-regulation of adhesion molecules and chemokines, as well as inhibition of leukocyte migration [198].…”
mentioning
confidence: 99%